GENDER DALAM PERSPEKTIF ISLAM - Nurlaila Al-Aydrus (Pusat Studi Gender dan Anak, IAIN Palu, 2023)
Islam is lifelyhood system that leads people to understand the reality of life. Islam is also a global structure revealed from Allah as rahmatan li al-‘Alamin. Concequencely, Allah created human beings (men and women) as His representation (Khalifah) in this world which have responsibilies to save and stabilze nature as well as to save human civilization. Therefore, both women and men have equal and comprehensive roles as human beings. Gender theory and concept seem easy and is difficult to apply as they need procedures and support from community, if gender is a principa choice for balancing individual roles in the global community. The survey results show that although the public's perception of gender equality is still weak, it is widely practiced and accepted in society. This is demonstrated by the realization of equal rights for children in education, equal division of household tasks between boys and girls, freedom to make decisions and express opinions, as well as freedom to make decisions within the family. Gender equality in the family is a good thing for society as long as it does not conflict with human nature and religious values ​​prevailing in society.